The dynamics of asymmetry among fertility, income inequality and financial development in Bangladesh - Humaira Husain (World Development Sustainability, 2022)
This research studies the extent of asymmetric responses of general fertility rate with financial development and income inequality in Bangladesh utilizing annual data from 1984-2019. We employ both linear and non- linear autoregressive distributed lag methodologies. Our study identifies a long run stable equilibrium among fertility rate, financial development and income inequality under assumptions of symmetric and asymmetric relationships between fertility and each of the control variables. Findings suggest effects of positive and negative shocks in financial development have negative and significant influence on the fertility rate in the long run. Therefore, in Bangladesh old age security hypothesis does not hold in the long run. Findings affirm that there are significant long run and short run asymmetries between fertility and financial development. However, there exists no significant short run and long- run asymmetries between fertility and Inequality. Families consider the ‘trade-off’ between quality and quantity of the children. Government could provide subsidy to private and informal sector to reduce the opportunity cost of rearing children for low- income families. Government could also support employment opportunities for women in non -conventional agricultural farming sector such as mixed cropping and floriculture